2020
DOI: 10.21873/cgp.20223
|View full text |Cite
|
Sign up to set email alerts
|

TIP60/P400/H4K12ac Plays a Role as a Heterochromatin Back-up Skeleton in Breast Cancer

Abstract: Background/Aim: In breast cancer, initiation of carcinogenesis leads to epigenetic dysregulation, which can lead for example to the loss of the heterochromatin skeleton SUV39H1/H3K9me3/HP1 or the supposed secondary skeleton TIP60/P400/H4K12ac/BRD (2/4), which allows the maintenance of chromatin integrity and plasticity. This study investigated the relationship between TIP60, P400 and H4K12ac and their implications in breast tumors. Materials and Methods: Seventy-seven patients diagnosed with breast cancer were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…SUV39H1 forms the SUV39H1/H3K9me3/HP1 structure, which maintains chromatin compaction and inhibits transcription in the heterochromatin region containing inactive oncogenes. Loss of this structure during breast cancer carcinogenesis leads to oncogene transcription (17). Previous studies have also demonstrated that the inhibition of SPRY4 expression, a factor known to suppress migration and stem cell-related properties in breast carcinoma cells (18), can be achieved through the recruitment of SUV39H1 by lncRNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…SUV39H1 forms the SUV39H1/H3K9me3/HP1 structure, which maintains chromatin compaction and inhibits transcription in the heterochromatin region containing inactive oncogenes. Loss of this structure during breast cancer carcinogenesis leads to oncogene transcription (17). Previous studies have also demonstrated that the inhibition of SPRY4 expression, a factor known to suppress migration and stem cell-related properties in breast carcinoma cells (18), can be achieved through the recruitment of SUV39H1 by lncRNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…21 HAT1 catalyzes the acetylation of newly synthesized histone H4 at lysines 5 and 12 (H4K5 and H4K12), 19,20,22 and can be recruited to the promoter or enhancer region of a gene by histone modification enzymes to enhance gene transcription. 23,24 Overexpressed HAT1 regulates tumor immunity by increasing programmed death-ligand 1 expression in pancreatic cancer. 25 Recently, our group reported that HAT1 is able to promote HBV replication by modulating H4K5 and H4K12.…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously found that HBV could upregulate HAT1 through the HBx‐activated transcription factor Sp1 21 . HAT1 catalyzes the acetylation of newly synthesized histone H4 at lysines 5 and 12 (H4K5 and H4K12), 19,20,22 and can be recruited to the promoter or enhancer region of a gene by histone modification enzymes to enhance gene transcription 23,24 . Overexpressed HAT1 regulates tumor immunity by increasing programmed death‐ligand 1 expression in pancreatic cancer 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Histone H4 acetylation at lysine 12 (H4K12ac) recruits DDR proteins and has been associated with chromatin restoration, increased transcription, and is responsible for interaction with other proteins in the chromatin structure (Hunt et al 2013). Levels of H4K12ac can be dependent on estrogen receptor α (ERα) activity (Nagarajan et al 2015) and decreased H4K12ac protein levels are observed in breast tumors (Idrissou et al 2020), potentially indicating that tissues with ER, including the ovary, can be targeted by alterations in levels of H4K12, leading to adverse effects.…”
Section: Discussionmentioning
confidence: 99%